Development of PjBL-Based Science Teaching Materials Integrated with Gendang Beleq Ethnoscience on Sound Concepts to Improve Students’ Science Process Skills - Ikhsan, Lalu Moh Nur; Herayanti, Lovy; Dewi, Ika Nurani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aimed to develop PjBL-based science teaching materials integrated with Gendang Beleq ethnoscience on sound concepts to improve students’ Science Process Skills (SPS). The study employed a Research and Development (R&D) approach, followed by a quasi-experimental effectiveness test using a nonequivalent control group design. The research subjects were eighth-grade students at SMP Negeri 2 Sakra, consisting of 61 students in the experimental group and 62 students in the control group. The developed products included the learning objective flow (ATP), teaching modules, student teaching materials, project worksheets, SPS test instruments, assessment rubrics, validation sheets, observation sheets, and teacher and student response questionnaires. Data were collected through expert validation, observation, questionnaires, pretest, and posttest. The data were analyzed using descriptive statistics, N-gain, the Shapiro-Wilk normality test, Levene’s homogeneity test, and Welch Robust ANOVA. The results showed that the teaching materials obtained an average validity score of 3.77, which was categorized as valid. Product practicality reached 88.78%, classified as highly practical; learning implementation reached 89.69%, classified as very well implemented; and student activity reached 87.15%, classified as highly active. The improvement in SPS in the experimental group yielded an N-gain score of 0.711, categorized as high, which was higher than that of the control group, which obtained an N-gain score of 0.616, categorized as moderate. The Welch Robust ANOVA results showed a significant difference between the experimental and control groups in both posttest and N-gain scores. Therefore, the PjBL-based science teaching materials integrated with Gendang Beleq ethnoscience were valid, highly practical, and effective in improving students’ SPS. The integration of Gendang Beleq provides a concrete local cultural context that enables students to connect the concepts of vibration, frequency, amplitude, resonance, and sound reflection through direct scientific experience.